Multicolor emission of Tb3+/Eu3+ co-doped poly(methyl methacrylate) for optical fibre technology - Miluski, Piotr; Kochanowicz, Marcin; Zmojda, Jacek; Dorosz, Dominik (Photonics Letters of Poland, 2017)
The article presents multicolor emission observed in poly(methyl methacrylate) specimens co-doped by trivalent terbium and europium ions. The bright luminescence was obtained using organometallic complexes of lanthanides and energy transfer antenna effect. Spectroscopic characterization exhibit wide excitation spectrum according to chelating structure of used complexes and characteristic Tb3+ and Eu3+ emission peaks in luminescence spectra. The calculated CIE 1931 chromaticity coordinates confirm that colorful emission from green to red can be obtained using proposed materials. Full Text: PDF References J.-H. Jou, M.-C. Sun, H.-H. Chou, C.-H. Li, "White organic light-emitting devices with a solution-processed and molecular host-employed emission layer", Appl. Phys. Lett. 87, 043508 (2005). CrossRef R. Mac Ciarnain, D. Michaelis, T. Wehlus, A. F. Rausch, N. Danz, A. Brauer, A. Tünnermann, "Emission from outside of the emission layer in state-of-the-art phosphorescent organic light-emitting diodes", Organic Electronics 44, 115 (2017). CrossRef G. Williams, C. Backhouse, H. Aziz, "Integration of Organic Light Emitting Diodes and Organic Photodetectors for Lab-on-a-Chip Bio-Detection Systems", Electronics 3, 43 (2014). CrossRef P. Miluski, D. Dorosz, M. Kochanowicz and J. Żmojda, "Fluorescent polymeric optical fibre illuminator", Electronics Letters, 52, 18 (2016). CrossRef L. Bilro, N. Alberto, J. L.Pinto, R. Nogueira, "Optical Sensors Based on Plastic Fibers", Sensors 12, 12184 (2012). CrossRef P. Miluski, D. Dorosz, J. Żmojda, M. Kochanowicz, J. Dorosz, "Luminescent Polymer Optical Fibre Sensor for Temperature Measurement", Acta Phys. Pol. A 127, 730 (2015) CrossRef C. Lethien, C. Loyez, J. P. Vilcot, N. Rolland, P. A. Rolland, "Exploit the Bandwidth Capacities of the Perfluorinated Graded Index Polymer Optical Fiber for Multi-Services Distribution", Polymers 3, 1006 (2011). CrossRef J. Zubia, J. Arrue, "Plastic Optical Fibers: An Introduction to Their Technological Processes and Applications", Opt. Fiber Technol. 7, 101 (2001). CrossRef N. Sultanovaa, S. Kasarovaa, I. Nikolov, "Dispersion Properties of Optical Polymers", Acta Physica Polonica A 116, 585 (2009). CrossRef J. Arrue, F. Jiménez, I. Ayesta, M. Asunción Illarramendi, J. Zubia, "Polymer-Optical-Fiber Lasers and Amplifiers Doped with Organic Dyes", Polymers 3,1162 (2011). CrossRef P. Miluski, M. Kochanowicz, J. Żmojda, "Spectroscopic investigation of organic co-doped PMMA for optical fiber technology", Journal Of Optoelectronics And Advanced Materials, 19, 379 (2017). DirectLink P. Miluski, M. Kochanowicz, J. Żmojda, and D. Dorosz, "Emission properties and energy transfer in Perylene-Rhodamine 6 G co-doped polymeric fiber", Chinese Optics Letters 14, 12, 121602 (2016). CrossRef H. Liang, Z. Yang, L. Xiao, F. Xie, " Radiative transition probability of a europium (III) chelating polymer", Optoelectronics And Advanced Materials ? Rapid Communications 4, 9, 1396 (2010). CrossRef H. Jiu, J. Ding, Y. Sun, J. Bao, C. Gao, Q. Zhang, "Fluorescence enhancement of europium complex co-doped with terbium complex in a poly(methyl methacrylate) matrix", Journal of Non-Crystalline Solids 352, 197 (2006). CrossRef K. Kuriki, S. Nishihara, Y. Nishizawa, A. Tagaya, Y. Koike, Y. Okamoto, "Spectroscopic properties of lanthanide chelates in perfluorinated plastics for optical applications", Journal of the Optical Society of America B 19, 8, 1844 (2002). CrossRef P. Miluski, M. Kochanowicz, J. Żmojda, D. Dorosz, "Luminescent properties of Tb3+-dopedpoly(methyl methacrylate) fiber" Chinese Optics Letters, 15, 7, 070602 (2017). DirectLink P. Miluski, M. Kochanowicz, J. Żmojda, D. Dorosz, "Properties of Eu3+ doped poly(methyl methacrylate) optical fiber", Optical Engineering, 56, 2, 027106 (2017). CrossRef D. Oh, N. Song and J.-J. Kim, "Plastic optical amplifier using europium complex", Proc. SPIE, 4282, (2001). CrossRef X. Xu, H. Ming, Q. Zhang, "Optical-transition probabilities of Nd3+ ions in polymer optical fibers", Optics Communications 199, 369 (2001). CrossRef Z.-Q. Zheng, H. Liang, H. Ming, Q.-J. Zhang, X.-H. Han, G.-Z. Wang, J.-P. Xie, "Optical Transition Probability of Sm 3+ Ions in a Polymer Optical Fibre", Chin. Phys. Lett. 21, 2, 291 (2004). CrossRef